Increased neocortical expression of the P2X7 receptor after status epilepticus and anticonvulsant effect of P2X7 receptor antagonist A‐438079. Issue 9 (28th June 2013) - Jimenez‐Pacheco, Alba; Mesuret, Guillaume; Sanz‐Rodriguez, Amaya; Tanaka, Katsuhiro; Mooney, Claire; Conroy, Ronan; Miras‐Portugal, Maria Teresa; Diaz‐Hernandez, Miguel; Henshall, David C.; Engel, Tobias
Summary Purpose ATP is an essential transmitter/cotransmitter in neuron function and pathophysiology and has recently emerged as a potential contributor to prolonged seizures (status epilepticus) through the activation of the purinergic ionotropic P2X7 receptor (P2X7R). Increased P2X7R expression has been reported in the hippocampus, and P2X7R antagonists reduced seizure‐induced damage to this brain region. However, status epilepticus also produces damage to the neocortex. The present study was designed to characterize P2X7R in the neocortex and assess effects of P2X7R antagonists on cortical injury after status epilepticus. Methods Status epilepticus was induced in mice by intraamygdala microinjection of kainic acid. Specific P2X7R inhibitors were administered into the ventricle before seizure induction, and cortical electroencephalography and behavior was recorded to assess seizure severity. P2X7R expression was examined in neocortex up to 24 h after status epilepticus, in epileptic mice, and in resected neocortex from patients with pharmacoresistent temporal lobe epilepsy (TLE). In addition, the induction of P2X7R after status epilepticus was investigated using transgenic P2X7R reporter mice, which express enhanced green fluorescent protein under the control of the p2x7r promoter. Key Findings Status epilepticus resulted in increased P2X7R protein levels in the neocortex of mice. Neocortical P2X7 receptor levels were also elevated in mice that developed epilepsy after status epilepticus and in resected neocortex from patients with pharmacoresistent TLE. Immunohistochemistry determined that neurons were the major cell population transcribing the P2X7R in the neocortex within the first 8 h after status epilepticus, whereas in epileptic mice, P2X7R up‐regulation occurred in microglia as well as in neurons. Pretreatment of mice with the specific P2X7R inhibitor A‐438079 reduced electrographic and clinical seizure severity during status epilepticus and reduced seizure‐induced neuronal death in the neocortex. Significance Our findings identify neurons in the neocortex as an important site of P2X7R up‐regulation after status epilepticus and in epilepsy, and provide support for the possible use of P2X7R antagonists for the treatment of status epilepticus and prevention of seizure‐induced brain damage.